2023
DOI: 10.1371/journal.pone.0282033
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic efficacy of Holarrhena pubescens against Raillietina spp. of domestic fowl through ultrastructural, histochemical, biochemical and GLCM analysis

Rachita Saha,
Manjil Gupta,
Rima Majumdar
et al.

Abstract: Globally, traditional knowledge systems are a powerhouse of information which can revolutionise the world, if decoded accurately and logically. Plant-based ethno-traditional and folklore curatives/medicines has a firm basis in the psyche of the common masses of West Bengal and Holarrhena pubescens is a representative example of it. This article communication on depicting the anthelmintic efficacy of ethanolic extract and Ethyl acetate fraction of the stem bark of Holarrhena pubescens against the cestode Railli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
2
2
0
Order By: Relevance
“…Additionally, the plant extract distorts the surface topography and subcellular structures. These ndings align with previous studies utilizing different plant extracts [39,41,42,57,65,66].…”
Section: Tem Observationssupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, the plant extract distorts the surface topography and subcellular structures. These ndings align with previous studies utilizing different plant extracts [39,41,42,57,65,66].…”
Section: Tem Observationssupporting
confidence: 92%
“…Scanning electron microscopy (SEM) studies have revealed distortions in the smooth texture of the tegument, as well as cracking and folding in treated worms, which are likely to impede nutrient uptake and energy metabolism in the parasite. Similar tegumental alterations caused by phytoproduct treatments have been documented by numerous researchers [35,41,42,57,[62][63][64].…”
Section: Sem Observationssupporting
confidence: 78%
See 2 more Smart Citations